2019
DOI: 10.1161/circheartfailure.119.005962
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Regulation of LRG1 by TGF-β1 and PPAR-β/δ Modulates Chronic Pressure Overload–Induced Cardiac Fibrosis

Abstract: Background: Despite its established significance in fibrotic cardiac remodeling, clinical benefits of global inhibition of TGF (transforming growth factor)-β1 signaling remain controversial. LRG1 (leucine-rich-α2 glycoprotein 1) is known to regulate endothelial TGFβ signaling. This study evaluated the role of LRG1 in cardiac fibrosis and its transcriptional regulatory network in cardiac fibroblasts. Methods: Pressure overload–induced heart failure was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…Akt is essential for NOX-independent NETosis ( 33 ). Furthermore, we demonstrated that LRG1-mediated NET formation is dependent on activation of the Akt pathway through TGFβ type I receptor ALK5, which is in agreement with LRG1-mediated TGFβ signaling in ECs ( 11 ), fibroblasts ( 34 ), glioma cells ( 46 ), and T-helper 17 cells ( 47 ). We further demonstrated that Lrg1 −/− mice are resistant to diabetes-induced delay in wound closure, especially during the inflammatory phase, which is likely due to its role in NETosis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Akt is essential for NOX-independent NETosis ( 33 ). Furthermore, we demonstrated that LRG1-mediated NET formation is dependent on activation of the Akt pathway through TGFβ type I receptor ALK5, which is in agreement with LRG1-mediated TGFβ signaling in ECs ( 11 ), fibroblasts ( 34 ), glioma cells ( 46 ), and T-helper 17 cells ( 47 ). We further demonstrated that Lrg1 −/− mice are resistant to diabetes-induced delay in wound closure, especially during the inflammatory phase, which is likely due to its role in NETosis.…”
Section: Discussionsupporting
confidence: 78%
“…7 G ). LRG1 was previously reported to signal through TGFβ type I receptor activin-like kinase 5 (ALK5) in non-ECs ( 34 ). For elucidation of whether LRG1-induced NETosis and Akt activation are dependent on ALK5, ALK5 was inhibited by SB431542, resulting in a complete abrogation of LRG1-induced phosphorylation of Akt and H3Cit ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study states that the reduced expression of LRG1 is connected to the increased TGF‐β1 activity during the cardiac remodelling process in response to injury 23 . Moreover, LRG1 deletion can lead to excessive activation of TGF‐β signalling pathway, leading to increased expression of TGF‐β1 and p‐Smad2/3 24 . A strong relationship between miR‐497 and Smad7 has been recorded in the literature that the expression of miR‐497 was inversely correlated with the Smad7 expression in breast cancer tissues and oral squamous cell carcinoma 25,26 …”
Section: Discussionmentioning
confidence: 98%
“…A previous study states that the reduced expression of LRG1 is connected to the increased TGF-β1 activity during the cardiac remodelling process in response to injury 23. Moreover, LRG1 deletion can lead to excessive activation of TGF-β signalling pathway, leading to increased expression of TGF-β1 and p-Smad2/3 24. A strong relationship between miR-497…”
mentioning
confidence: 94%
“…This observation suggests a pro-tumorigenic role of LRG1. Surprisingly, the LRG1 promoter has two putative PPAR response elements [ 91 ]. The expression of LRG1 is increased by a PPARβ/δ agonist, GW501516, which strongly suggests that LRG1 is a direct target of PPARβ/δ [ 91 ].…”
Section: The Roles Of Ppars In Stromal Cells In the Tumor Microenvironmentmentioning
confidence: 99%